(3JPcQI GdcGMdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s
(3ChdgG (B:s
(3hUd cJGHc CjgG GdaGVd MaXc Gddg HQCaJg hCQTOc Edi GdUhGH HQMeJI , JSCdfi ajg Yf NhGeY cJH LGdjfhS s
(3BNQgG (B:s
(3aEf cGf Rdd aCUdMg HYO Cf JfYe GdfXQ ajg hCf JLYd ecGaCJi Ydi bVGA MGLJc cKQI GdOYGA s
(3hQJHgG Ydi KdGK ebGdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B43 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B42) s
Keywords: (3GdWHs